2021
DOI: 10.1111/1751-7915.13751
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis and biochemical properties of laccase enzymes from two Pediococcus species

Abstract: Prokaryotic laccases are emergent biocatalysts. However, they have not been broadly found and characterized in bacterial organisms, especially in lactic acid bacteria. Recently, a prokaryotic laccase from the lactic acid bacterium Pediococcus acidilactici 5930, which can degrade biogenic amines, was discovered. Thus, our study aimed to shed light on laccases from lactic acid bacteria focusing on two Pediococcus laccases, P. acidilactici 5930 and Pediococcus pentosaceus 4816, which have provided valuable inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…In comparison with the MCO from P. acidilactici, no degradation of histamine and putrescine was observed for this enzyme, although it showed less than 20% degradation of total BAs [31]. Other studies demonstrated only 10% and 5% degradation of histamine and putrescine by MCOs from LAB [32,57]. At present, the degradation rate of BAs using MCOs was lower than that using LAB strains [26], degradation of BAs by food-grade enzymes is still a promising method as the expression level of enzyme can be easily enhanced, and the catalytic efficiency of enzymes can be improved by various molecular modification strategies [58][59][60].…”
Section: Degradation Of Bas By Mcob Lsmentioning
confidence: 65%
See 1 more Smart Citation
“…In comparison with the MCO from P. acidilactici, no degradation of histamine and putrescine was observed for this enzyme, although it showed less than 20% degradation of total BAs [31]. Other studies demonstrated only 10% and 5% degradation of histamine and putrescine by MCOs from LAB [32,57]. At present, the degradation rate of BAs using MCOs was lower than that using LAB strains [26], degradation of BAs by food-grade enzymes is still a promising method as the expression level of enzyme can be easily enhanced, and the catalytic efficiency of enzymes can be improved by various molecular modification strategies [58][59][60].…”
Section: Degradation Of Bas By Mcob Lsmentioning
confidence: 65%
“…The gene encoding multicopper oxidase has been verified in the genome of Lactobacillus curvatus G-1, and this enzyme exhibits capability in degradation of six common BAs including histamine, tyramine, and putrescine [26]. MCO from Lactobacillus plantarum J16 can degrade tyramine, histamine, and putrescine, while the one from Pediococcus acidilactici CECT 5930 degrades tyramine only [27][28][29]. MCO from Lactobacillus fermentum Y29 showed activity against a broad range of substrates (histamine, tyramine, tryptamine, phenylethylamine, putrescine, cadaverine, and spermidine), and was found to be tolerant to 18% (w/v) NaCl [30].…”
Section: Introductionmentioning
confidence: 99%
“…Another obvious difference in structure between asco-laccase MtL and basi-laccase CcLcc5 with possible negative regulatory effects on the enzymatic activity is the C-tail, which MtL has extra (Figure 1). Such C-tails are also typical of ascolaccases and act as a plug to block the water channel of the enzymes (Andberg et al, 2009;Pardo and Camarero, 2015;Ernst et al, 2018;Olmeda et al, 2021). It is conceivable that the function of the plug in asco-laccase MtL can be impaired by irregular structural effects caused by the hydrophilic Indulin AT.…”
Section: Oxygen Consumption Measurementsmentioning
confidence: 99%
“…2) is a dioxygen oxidoreductase that contains four copper atoms in the catalytic center. Laccases are widely distributed in fungi, higher plants, insects, and some bacteria [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] and belong to the family of blue multi-copper oxidases (BMCOs) [ 8 , 9 , 10 ]. The wide range of substrates catalyzed by laccase contributes to the diversity of laccase function [ 11 ].…”
Section: Introductionmentioning
confidence: 99%